Comparative evaluation of hybrid seed production of bitter gourd in rainy and spring-summer season - Sandra, Nagamani; Basu, Sudipta; Behera, T.K. (Indian Journal of Horticulture, 2018)
A study was conducted with the parental lines of two popular bitter gourd hybrids; Pusa Hybrid-1 and Pusa Hybrid-2 to assess the effect of season on pollination behaviour, fruit setting, fruit yield and seed quality with respect to hybrid seed production. The hybrid seed production was carried out by hand pollination for four weeks in spring summer and rainy season. The results showed high pollen viability (R: 97.63-100%, S-S: 90- 95%) and stigma receptivity in both the seasons however higher fruit yield, fruit traits (weight, length, width) were achieved in rainy season whereas the fruit setting percentage (80-90%) and seed quality were superior in the spring-summer season. Among the weeks of pollination compared, first and second weeks of pollination i.e. last week of April to first week of May in spring summer, third and fourth week of September in rainy season were found to be better for hybrid seed production than later weeks of pollination in both the seasons.